Analysis of selected methods of diagnostics and physiotherapy of pes plano-valgus in children - Pardus, Kamila; Stencel-Gabriel, Krystyna; Kurdyś, Paulina; Konwant, Dawid; Nowak, Urszula (Journal of Education, Health and Sport, 2022)
Introduction: Flat feet is one of the most common posture defects among children and it usually co-occurs with valgus of the heels, which is called pes plano-valgus. There are many diagnostic methods and physiotherapeutic activities that allow for early detection and appropriate correction of the defect. The use of non-surgical methods may allow the child to avoid surgery in the future. Aim and Methods: Review and analysis of the current scientific literature on the diagnosis and physiotherapy of plano-valgus feet in children. Conclusions: In the diagnostic process, there are many static and dynamic methods for the assessment of plano-valgus foot among children. Special devices such as plantoconturograph, podoscope, and pedobarographic mat are used in the diagnosis of feet in children and have proven to be helpful in the detailed analysis of foot defects. However, an extensive range of physiotherapeutic methods allows for comprehensive treatment using not only corrective exercises, but also physical therapy treatments in order to relieve pain and accelerate recovery. Orthopedic appliances, such as supination insoles, also play an important role in the treatment. The best results were seen in the use of comprehensive treatment and multiple terapeutic methods. Early detection and correct diagnosis of foot abnormalities allow for appropriate treatment with the use of a wide range of physiotherapy methods. This increases the chances of restoring normal foot functions among children and reducing pain with other abnormal symptoms.